Interaction of clopidogrel and statins in secondary prevention after cerebral ischaemia – a randomized, double-blind, double-dummy crossover study - Siepmann, Timo (Br J Clin Pharmacol, 2014)
AIMS: Variability in responsiveness to clopidogrel is a clinical problem in secondary prevention after cerebral ischaemia which has been suggested to be linked to competitive metabolization of clopidogrel and cytochrome P450 (CYP) 3A4-oxidated statins such as simvastatin. We assessed the hypothesis that simvastatin, in contrast to CYP 2C9-metabolized fluvastatin, reduces clopidogrel-mediated platelet inhibition. METHODS: We performed a randomized, double-blind, double-dummy, two period crossover study in 13 patients with cerebral ischaemia (8F, 5 M), aged 64.1 ± 8.0 years (mean ± SD). After a 14 day period in which all patients received 75 mg clopidogrel day(−1), patients additionally received either 20 mg simvastatin day(−1) or 80 mg fluvastatin day(−1) for 14 days. Regimens were crossed over after a 14 day wash-out period and switched regimens were continued for another 14 days. Platelet aggregation, clopidogrel active metabolite (CAM) plasma concentrations and routine laboratory parameters including prothrombin time (PT) Quick percent value were assessed at baseline and following each treatment phase. RESULTS: Clopidogrel reduced platelet aggregation in all patients as expected. Platelet aggregation and CAM plasma concentrations were unaltered when simvastatin or fluvastatin was added to clopidogrel. Simvastatin decreased PT Quick percent value (decrease from 109 ± 10.5% to 103 ± 11%, P < 0.05) when combined with clopidogrel but there was no such change following treatment with fluvastatin and clopidogrel. CONCLUSIONS: Our data indicate that treatment with CYP 3A4-metabolized simvastatin does not jeopardize clopidogrel-mediated inhibition of platelet aggregation. After co-administration of simvastatin and clopidogrel we observed a decrease in the PT Quick percent value which could be due to simvastatin-induced reduction of activity of prothrombin fragment 1 + 2.